Bicycle tourism and rural community development: an asset based approach - Broadaway, Sally (Kansas State University, 2012)
As bicycle tourists seek interesting experiences along low traffic roads, rural communities are poised to embrace bicycle tourism as a community development strategy. Asset based community development provides a methodology for communities to utilize assets that already exist within their communities to meet the needs of these tourists. The community capitals framework then provides a platform for analyzing and discussing the existing assets, as well as helping hone in on ways communities can develop further. The Sunken Lands region of Northeast Arkansas is one such rural region seeking to embrace bicycle tourism. Two case studies of communities that have capitalized on their existing assets to accommodate bicyclists were completed to explore potential for using the community capitals framework to guide pursuit of bicycle tourism. A snowball approach to interviewing community members in Collinwood, Tennessee and Farmington, Missouri was used to discover the details of bicycle accommodations, the processes of pursuing bicycle tourism, the people and groups involved, the types of assets used, and any challenges faced in implementation. Additionally, existing literature was used to substantiate each case and provide a more robust community picture. Emerging from the case studies were commonalities that aligned with the community capitals framework and Emery and Flora’s (2006) theory that community change is driven by social capital. The result is a tool that aligns community assets with the needs of bicycle tourists with the community capitals framework.
Keywords: Asset Based Community Development; Bicycle Tourism; Rural; Area Planning and Development (0341); Recreation and Tourism (0814)